The Influence of Demographic Transition Factors on the Demographic Dividends in the Republic of Kazakhstan - M. S. Bekturganova; G. K. Kenzhegulova; A. K. Jussibaliyeva; S. S. Tleuberdiyeva (Экономика: стратегия и практика, 2022)
The purpose of this article is to explore the relationship between factors of demographic transition and the demographic dividend in developing countries on the example of Kazakhstan. This literature review made it possible to identify two main factors that indirectly impact economic growth: the working-age population and the labor force. Correlation and regression analyses were conducted to investigate the relationship between these factors, taking into account urban and rural areas. The SPSS program was used to confirm four hypotheses. Where Working Age Total is the dependent variable and Women Working Age Urban Population, Women Working Age Rural Population are independent variables for the first two hypotheses. In the third and fourth hypotheses, Labor Force Total is the dependent variable, and Fertility Rate, Fertility Rate Urban, Fertility Rate Rural, Death Rate, Death Rate Urban, Death Rate Rural are independent variables. Data from the official open source information of the Bureau of National Statistics between 2007-2020 was used. According to the results, three hypotheses were partially accepted, one was rejected. The results showed little effect of changing demographic structure in rural areas on the working-age population, except for mortality rate. The birth rate has a positive impact on the working-age population only in cities. The female population of working age, although predominant in terms of the number, has a negligible effect on the labor force. The results of this study can be used to develop and improve existing programs and strategies for managing demographic factors by  the government at various levels and in science.